Images of Cultural Heritage in the Tourism Brand of Spain - A. A. Koroleva; E. P. Smolskaya; V. S. Davydkin; L. D. Novikova (Ибероамериканские тетради, 2024)
According to the theory of commodification, heritage is considered as a resource with its own economic value. The sphere of culture and heritage, in particular, are increasingly perceived as a factor of sustainable development. One of the key infrastructure functions of heritage is its role in the formation of an attractive image of a territory, of a tourist destination, in our case. In the empirical part of the study, we analyze 18 promotional videos dedicated to cultural tourism, from the last 5 advertising campaigns of Turespaña. Promotional videos are short videos designed to promote a specific marketing initiative, sale, or event. They combine both advertising texts, images and music, achieving a synergistic effect on the target audience. World Heritage sites of Spain are most frequently used in promos: Antonio Gaudi’s architecture in Barcelona and its surroundings, the Alcazar of Segovia. Intangible heritage is represented, first and foremost, by the images of Spanish cuisine, i.e. the Mediterranean diet and winemaking. We analyze not only lexical and grammatical components of promotion texts, but also their stylistic features, some additional connotations and special communicative functions. The use of music in promos plays an important role in making an emotional impact, as music is generally associated with a particular emotion, memory, thought, or it might even give us a strong incentive to act.